Technology and higher education: an Australian study - Issa, Tomayess; Issa, Theodora; Chang, Vanessa (Common Ground Publishing LLC, 2012)
The aim of this paper is to provide a first-hand experience of deploying latest technology for not only allowing the submission of assignments by students electronically, but also the provision of feedback on these assignments to students. In this Australian case study, the lecturers used and continue to use the software ‘Audacity’ and ‘echo360’ to communicate with students providing them with feedback on their assessments, general feedback for the benefit of the whole class, directed to all campuses, and weekly lectures’ summaries. The findings suggest that the use of such technology develops a range of skills that would enhance students’ interest in the unit, and their life-long learning. This paper provides an account derived from the examination of data collected from lecturers and students of undergraduate units.